Ground-fault detection in multiple source solidly grounded systems via the single-processor concept for circuit protection - Valdes, M.E.; Lavoie, G.; Papallo, T.; Premerlani, W. (IEEE transactions on industry applications, 2006)
Modern power distribution systems often contain multiple power sources integrated within one system. A simple variant may be the common double-ended substation, which can be further complicated by an additional emergency or alternate sources. This presents significant complexity to the designer attempting to design a protection system that will not be fooled by circulating neutral currents. The authors describe how the "single processor concept for circuit breaker protection and control" (M. E. Valdes et al., Proc. PCIC, 2003, pp. 267-275) provides ways to address this sensing problem. One such method is described in further detail. Handling of resistance-grounded systems will be the subject of a related paper.